Increasing the technical efficiency of bead mills for ultra-fine grinding of components of medicinal and cosmetic products - Hrininh-Hera, Kateryna; Gubenia, Oleksii; Zhytnetskyi, Artem; Samarchuk, Serhii (My University, 2024)
Research was conducted with the aim of determining changes in the particle size distribution of drug and cosmetic suspensions during processing in a bead mill and improving the efficiency of its operation. The obtained results are useful for choosing rational modes of operation of the bead mill and conducting the grinding process, in particular, choosing the construction of working elements, kinematic parameters, grinding time.
Keywords: grinding; наддрібне подрібнення; бісерний млин; bead mill; кафедра мехатроніки та пакувальної техніки